Caribbean Report 04-01-1995 - Crosskill, Hugh (anchor); Powell, Chris (interviewee); Foreman, Martin (interviewee); Lloyd, Waveney (interviewee); Smith, Henry (interviewee); Coughlan, Geraldine (correspondent) (The British Broadcasting Corporation, 1995)
Hugh Crosskill, anchor, reports that the Caribbean is urged to introduce sex education in primary schools as the number of AIDS cases continues to rise. Martin Foreman comments that while AIDS have become an endemic disease, education has worked overall. He argues for early sex education for all young people between the ages of 10 and 11. The illness of Jason Lloyd, son of Clive Lloyd, former cricket captain of the West Indies is examined. Jason became ill after a booster injection against measles. Henry Smith of the Caribbean Epidemiology Centre (CAREC) responded to questions on whether the illness could have been a direct result of the booster shot and if older children should receive booster shots. Geraldine Coughlan reports on the investigations into Air St. Bart's purchase of three Australian planes by the General Direction of Taxes Office in Paris. Successive incidents resulted in a ban on company flights as designated safety level repairs were not carried out. The report wraps up as Vincentians have their say on the knighthood of their Prime Minister James Mitchell.
1. Headlines with Hugh Crosskill (00:00-00:29)
2. Report on statistics released by the World Health Organization (WHO) on the officially reported cases of AIDS around the world (00:30-01:15)
3. Interview with WHO spokesman, Chris Powell (01:16-01:37)
4. Hugh Crosskill interviews Martin Foreman on AIDS education programmes in the Caribbean (01:38-05:19)
Keywords: Sex instruction -- Education -- Caribbean Area; Health education -- Caribbean Area; AIDS (Disease) -- Caribbean Area; HIV infections -- Caribbean Area; AIDS (Disease) -- Prevention; HIV infections -- Prevention; Youth; Liquidation; Aeronautics -- Safety measures; Local service airlines -- Saint Martin; Knights and knighthood -- Saint Vincent and the Grenadines